The Effect of Product Quality, Price and Distribution Channels on Purchasing Decisions - Wijaya, Nur Qoudri (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine the influence of product quality, price, and distribution channels on purchasing decisions in the keris craftsman center in Aeng Tong-Tong Village, Saronggi Subdistrict, Sumenep Regency. The research method used is quantitative with purposive sampling technique, collecting data through observation, questionnaires, and interviews. The research sample consists of 80 respondents measured using a Likert scale. The results show that product quality has a negative and significant effect on purchasing decisions. Conversely, price and distribution channels have a positive and significant effect on purchasing decisions. Thus, it can be concluded that there is an influence between product quality, price, and distribution channels on purchasing decisions, where these three variables are interrelated. These findings indicate the importance of appropriate pricing and distribution strategies to enhance purchasing decisions, although the expected product quality needs to be improved to yield better results.